Modeling Profil Aliran Pulp Slurry di Pipa Distribusi Produk Akhir Bleaching Plant - Simanjuntak, Thomson; Baharuddin (Department of Chemical Engineering, Faculty of Engineering, UNRI, 2022)
An understanding of the pulp slurries flow is the important step in the piping system design, piping is a means of transporting pulp in all production lines in the pulp and paper industry. Pulp slurries flow is a complex process flow, this is due to the interactions between the different phases and also due to the turbulent charactheristic of the flow as well. In this study, Computerized Fluid Dynamics (CFD) was utilized to develop a model with parameters obtained from the pulp slurry flow in the field to characterized pressure drop and velocity profile in the medium consitency pulp of 10%. CFD modeling uses Ansys Fluent with the Mixture method and the SIMPLE solver algorithm. The fully developed flow is at elevation of Y = 4.85 m and at direction of Z = -2.55 m and it is turbulent flow characteristics. The pressure drop along the pipe is 68401.2 Pascal.